The Effect of Selected Factors on Tax Revenue Mobilization in Ethiopia: The Case of Amhara Region - Tehulu, Tilahun Aemiro (The Economics and Finance Letters, 2019)
While many African countries raise 15% or more in tax revenue, some countries like Ethiopia still do not raise the necessary amount of resources to allow for the sound functioning of domestic institutions and basic service delivery. Therefore, this study investigated the perceived effect of selected factors on tax revenue mobilization in Ethiopia. Data is collected through a structured questionnaire and analyzed using univariate statistics namely one sample T-test and other descriptive statistics including proportions and means. The findings revealed that the political instability of the country has negatively affected the normal business operation of firms; reduced investments due to lower confidence of investors and negatively affected the taxable income of business firms. The results, however, revealed that closeness to general elections doesn’t affect normal business operation of firms. The findings also revealed that there is high corruption by tax officials in our region; taxpayer awareness creation to report any corruptive practices is also weak; measures by the tax authority to improve the accountability of tax officials are also limited or none and those corruptive practices have negatively affected the amount of tax the revenue office could mobilize. Finally, the study uncovered that the present tax audit practice does not reduce tax evasion and other irregularities in our region and that the awareness of taxpayers of tax audit per se doesn’t make the tax payers render a satisfactory tax return. We also found that the tax administrative structure lacks autonomy and there is the inadequacy of skilled and competent employees in the tax administration.